2020
DOI: 10.1111/eea.12958
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cold storage on life‐history traits ofAphidius matricariae

Abstract: Aphidius matricariae Haliday (Hymenoptera: Braconidae) is a polyphagous solitary endoparasitoid, attacking more than 40 species of aphids. This parasitoid is an important commercial product of many companies that produce biological control agents. Storage at low temperature increases the shelf life of many biocontrol agents, allowing companies to provide a steady and sufficient supply of insects for biocontrol programs. In the current study, the effects of cold storage of 1‐day‐old host mummies with A. matrica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…Although there are existing advantages, keeping parasitoids at sub-ambient temperatures adversely affects the fitness of some parasitoids [ 19 , 20 ]. Therefore, to minimize the parasitoid reproductive performance loss after cold storage, it is necessary to investigate the effect of cold storage on the biological parameters of parasitoids, which contributes to establishing technical constraints for their commercial production and application [ 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although there are existing advantages, keeping parasitoids at sub-ambient temperatures adversely affects the fitness of some parasitoids [ 19 , 20 ]. Therefore, to minimize the parasitoid reproductive performance loss after cold storage, it is necessary to investigate the effect of cold storage on the biological parameters of parasitoids, which contributes to establishing technical constraints for their commercial production and application [ 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, keeping parasitoids at a sub-ambient temperature can result in cold injuries and excessive consumption of energy reserves, resulting in undesirable effects on the quality and quantity of post-storage parasitoids [ 11 ]. Hence, to minimize losses in the performance of parasitoids after undergoing storage, packaging, and shipment, recent research has focused on optimizing the tradeoffs between quality and the cold storage protocol [ 12 , 13 , 14 ]. For braconid parasitoids against tephritid pests, the impacts of cold storage have been evaluated in several species, such as Psyttalia humilis (Silvestri), Psyttalia ponerophaga (Silvestri), Fopius arisanus (Sonan), and Diachasmimorpha longicaudata (Ashmead) (Hymenoptera: Braconidae); these works have provided a lot of valuable information for facilitating the practical application of biological control programs [ 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Coudron et al (2007) reported that a high percentage of adult Podisus maculiventris Say (Heteroptera: Pentatomidae) survived for 4 weeks at 10°C. Rezaei et al (2020) found that the pupae of Aphidius matricariae Haliday (Hymenoptera: Braconidae) could be stored for 15 d at 5°C without any detrimental effects. Larentzaki et al (2007) stored adult F. vespiformis for 3.5 weeks at 10.0 and 12.5°C, and found that the eggs could be stored for 4-5 weeks at 12.5°C.…”
Section: Discussionmentioning
confidence: 99%